Gratification In Indonesian Medical Practice - Istiana Sari; Darwati Darwati (Interdiciplinary Journal and Hummanity (INJURITY), 2023)
Medical world no miss from issue gratuities. In practice a doctor not only play a role as an expert in treat disease, but also required for always update and add science in accordance with development and progress technology. The role of sponsorship in medicine become one of the media support government programs in Educational Development Professionalism Sustainable. A doctor not allowed receive cash as form of sponsorship. Doctors in Indonesia need understand the law settings on sponsorship provided by the pharmacy company